Leveraging 3D Printing for Resilient Disaster Management in Smart Cities - Antreas Kantaros; Florian Ion Tiberiu Petrescu; Konstantinos Brachos; Theodore Ganetsos; Nicolae Petrescu (Smart Cities)
This work explores the transformative impact of 3D printing technology and disaster management within the context of smart cities. By evaluating various 3D printing technologies, such as desktop and large-scale printers, this research highlights their application in rapidly producing customized structures and essential supplies infrastructure components. Methods included the review of existing technologies, practical application in disasters scenarios. and the analysis of community engagement programs that enhance local preparedness and resilience through 3D printing. Case studies illustrate the significant benefits of integrating 3D printing technologies in disaster management. Findings indicate that while 3D printing offers rapid production and efficiency, disabilities such as high initial cost, regulatory issues, and the need for skilled operators must be addressed. This study concludes that with strategic collaboration and investment in the education and regulatory frameworks, 3D printing can significantly enhance urban resilience and sustainability, making it an invaluable tool for future smart cities. This research underscores the potential of 3D printing to significantly aid disaster management practices, fostering more adaptive and efficient urban environments.